2006
DOI: 10.1038/sj.pcan.4500901
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity focused ultrasound therapy for clinically localized prostate cancer

Abstract: The efficacy of high-intensity focused ultrasound (HIFU) used for the treatment of localized prostate cancers has been demonstrated over the past decade. We present our early results after HIFU used as a single session in patients with clinically localized prostate cancer. A total of 58 patients were treated using the Ablatherm HIFU device with or without transurethral resection of the prostate (TURP). HIFU failure was defined as the presence of a cancer remnant on repeated biopsies or three consecutive increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 24 publications
1
45
0
4
Order By: Relevance
“…In 1996, Gelet et al [26] reported a preliminary experience with an Ablatherm prototype in almost the same indications. From these first papers to the contemporary series, several publications with both devices have confirmed the HIFU efficacy as a primary procedure in the aforementioned indications with short-and mid-term results [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Outcome Measuresmentioning
confidence: 67%
See 2 more Smart Citations
“…In 1996, Gelet et al [26] reported a preliminary experience with an Ablatherm prototype in almost the same indications. From these first papers to the contemporary series, several publications with both devices have confirmed the HIFU efficacy as a primary procedure in the aforementioned indications with short-and mid-term results [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Outcome Measuresmentioning
confidence: 67%
“…In most cases, the PSA nadir is reached within 6 months following the procedure, making it possible to have early feedback on treatment efficacy. Many studies have demonstrated that the PSA nadir significantly predicts HIFU success [16,21,28]. Lee et al [16] proposed to carefully monitor those patients in whom the PSA nadir has not dropped below 0.5 ng/mL.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Two institutions [16,17] routinely perform a TURP at the same time as the patient receives HIFU, whereas the third institution [18] does not. These studies found negative post-HIFU biopsies in 80% to 87% of patients who underwent biopsies and a mean PSA nadir between 0.2 and 0.33 ng/mL reached within a mean of 8 weeks to 4.4 months after the procedure.…”
Section: High-intensity Focused Ultrasoundmentioning
confidence: 99%
“…These therapies are ablative, so that a threshold PSA appears most appropriate (e.g., PSA > 0.5 μg/L), but dynamic definitions as used for radiotherapy have also been proposed. 15,16 This will need to be addressed with top priority if focal therapy is to be studied in a systematic fashion.…”
Section: There Is No Role For Focal Therapy In Prostate Cancermentioning
confidence: 99%